PENGARUH INFLASI, TINGKAT SUKU BUNGA, DAN NILAI TUKAR RUPIAH TERHADAP HARGA SAHAM PT BANK BTPN SYARIAH YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2019-2021 - Marita Ayu Oktaviani; Nadia Roosmalita Sari (Faculty of Islamic Economic and Business (FEBI), Sayyid Ali Rahmatullah State Islamic University (UIN SATU) Tulungagung, 2022)
The purpose of this study is to find out the correlation of macroeconomic variables such as inflatin, interest rates, and the rupiah exchange rate with stock prices. Quantitative methods and purposive sampling techniques were adopted in this study. A total of 36 data as samples were taken using library and document methods. Multiple linear regression analysis was tested using software eviews 12. The results of the test and analysis both partially and simultaneously are: (1) the inflation variabel has no effect on stock prices, (2) the interest rate variabel has an effect on stock prices, (3) the exchange rate variable has an effect on stock prices, (4) variables of inflation, interest rates, and the rupiah exchange arte simultaneously affect stock prices.